2020
DOI: 10.1073/pnas.2005335117
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from internet search data shows information-seeking responses to news of local COVID-19 cases

Abstract: The COVID-19 outbreak is a global pandemic with community circulation in many countries, including the United States, with confirmed cases in all states. The course of this pandemic will be shaped by how governments enact timely policies and disseminate information and by how the public reacts to policies and information. Here, we examine information-seeking responses to the first COVID-19 case public announcement in a state. Using an event study framework for all US states, we show that such news incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
274
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 280 publications
(312 citation statements)
references
References 10 publications
19
274
2
Order By: Relevance
“…Thus, the trustor (to realize the practical act of trusting) needs a lower level of trust (as mental attitude). In our specific case, to trust the institution was the only possible choice; thus, the higher information request [ 2 ] was introduced as a control mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the trustor (to realize the practical act of trusting) needs a lower level of trust (as mental attitude). In our specific case, to trust the institution was the only possible choice; thus, the higher information request [ 2 ] was introduced as a control mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In this context of uncertainty and constant change, a strong need for information emerged [ 2 ], in order to understand what was going on: how the pandemic was evolving; to assess the actual risk to which all of us were subjected; to know community-level policies or personal health strategies. Quarantine, social distancing, mass swab tests, school closures, and the use of personal protective equipment are just some of the highly restrictive measures adopted to deal with the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that people may respond more to the initial reopening announcement than to incremental changes in the degree of opening. Even before official state closures, attention to the coronavirus as measured by internet search behavior in a state increased suddenly when the state announced its first positive case (Bento et al, 2020). Earlier work on state closures suggests that mobility effects are largest for information-laden policy actions (Gupta et al, 2020).…”
Section: State Reopening Policiesmentioning
confidence: 99%
“…During the Zika virus epidemic in 2016, public attention was synchronized across US states, driven by news coverage about the outbreak and independent of the real local risk of infection [ 22 ]. With respect to the COVID-19 pandemic itself, a recent study clearly showed how Google searches for coronavirus in the United States spiked significantly immediately after the announcement of the first confirmed case in each state [ 23 ]. Several studies based on Twitter data have also highlighted how misinformation and low-quality information about COVID-19, although limited overall, spread before the local outbreak and rapidly expanded once local epidemics started [ 24 - 26 ].…”
Section: Introductionmentioning
confidence: 99%